2023
DOI: 10.1371/journal.pone.0281400
|View full text |Cite
|
Sign up to set email alerts
|

Ankle strategies for step-aside movement during quiet standing

Abstract: The mediolateral ankle strategy plays a crucial role in providing ankle stability in ground obstacle-avoidance behavior. This is achieved by changing basic walking patterns according to the characteristics of the obstacle. In daily life, it is more common to use step-aside movement (i.e., dodging step) for collision avoidance rather than side-stepping (i.e., widening standing base) when encountering an approaching pedestrian or bicycle. While studies have been conducted on the mediolateral ankle strategy contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 40 publications
3
5
0
Order By: Relevance
“…Multiple linear regression analyses were performed for the left CoP (left CoPx, left CoPy) and left GRF (left F-GRF) models. PL contraction dominated the mediolateral ankle strategy in step-aside movements ( Table 1 ), which aligns with our previous findings [ 1 ]. F-GRF generation was strongly correlated with independent variables in the left push phase for both movements, indicating that the combination of ankle muscle contraction and CoP displacement significantly influenced F-GRF generation.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Multiple linear regression analyses were performed for the left CoP (left CoPx, left CoPy) and left GRF (left F-GRF) models. PL contraction dominated the mediolateral ankle strategy in step-aside movements ( Table 1 ), which aligns with our previous findings [ 1 ]. F-GRF generation was strongly correlated with independent variables in the left push phase for both movements, indicating that the combination of ankle muscle contraction and CoP displacement significantly influenced F-GRF generation.…”
Section: Resultssupporting
confidence: 92%
“…Our results reveal significantly higher bilateral ankle muscle activation during step-aside movement than during straight walking in the selected period of the left push phase, particularly in the left PL muscle, as previously reported [ 1 ]. The results support our hypothesis that the CoP trajectories in the left push phase within the selected ROI would significantly differ.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Research conducted by Xie et al . [ 4 , 5 ], revealed that PAs may result from the internal initiation of movement (preparation to perform a certain activity). Similarly, Cleworth et al .…”
Section: Introductionmentioning
confidence: 99%